Censorship of “obscene” literary translations in Turkey: An analysis of two specific cases - (:unkn) unknown (John Benjamins Publishing Company, 2015)
This article analyzes the practice of literary censorship and court proceedings on grounds of obscenity in Turkey within the framework of two case studies: the Turkish translation of Pierre Louÿs’ Aphrodite: moeurs antiques (1896) and that (in 1985) of Henry Miller’s Tropic of Capricorn (1939). Both cases, with a time gap of almost half a century, demonstrate different details in the implementation of censorship and how they provoked reaction. The analysis makes it clear that the historical, ideological and political backdrop to each case had implications in terms of how translation was approached at different times in Turkish intellectual history in line with the function it was supposed to assume and how this bore upon the outcome of the censorship cases. © 2015 John Benjamins Publishing Company.
Keywords: Autonomy of the literary field; Banning of books; Censorship; Legal proceedings; Obscenity; Prosecution of translators